Accurate identification method for splitting process of medium-temperature-mixed fully-recycled asphalt mixture
Through the splitting test and strain measurement of medium-temperature mix fully regenerated asphalt mixture, the three stages of the splitting process are accurately distinguished and the splitting energy parameters are calculated, which solves the problem that the cracking performance cannot be accurately evaluated in the existing technology, and achieves a more accurate evaluation of crack resistance.
Patent Information
- Application Number
- CN202411289244.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art lacks an accurate identification method for the splitting process of medium-temperature mix fully regenerated asphalt mixture, and cannot accurately evaluate and compare its cracking performance, resulting in large errors in the evaluation of cracking resistance.
By obtaining the Marshall test piece of medium-temperature mix fully regenerated asphalt mixture, performing a split test, obtaining the load-vertical displacement curve and the full-field strain-loading time relationship, calculate the average value of the full-field horizontal strain-loading time curve, and is divided into slow growth , rapid growth and decline stages, determine the crack initiation, development and failure stages, accurately distinguish the critical points of the three-stage fracture process, and calculate the split energy parameters.
The precise evaluation of the cracking performance of medium-temperature mix fully regenerated asphalt mixture is achieved, the accuracy and comparability of crack resistance evaluation is improved, and it is suitable for mixing materials with different split strengths, reducing evaluation errors.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road engineering, and specifically to a method for accurately identifying the splitting process of a medium-temperature mixed fully recycled asphalt mixture. Background Art
[0002] Under the background of increasingly scarce resources, increasing environmental protection requirements, and increasing amounts of waste road materials, efficient and high-value recycling of RAP has become an urgent issue to be solved in my country's road transportation industry, and is also one of the key research directions supported by the state. Among them, medium-temperature mixed fully recycled asphalt mixture has good mixing and compaction properties, can achieve 100% RAP utilization, and does not require curing, greatly reducing the use of new aggregates and new asphalt binders, and has excellent economic and environmental benefits.
[0003] Medium-temperature mixed fully recycled asphalt mixture is mainly made of 100% old materials, and often has the characteristics of high fine material and aged asphalt content. The high powder-to-binder ratio and aged asphalt content are not conducive to the cracking performance of the mixture, which makes the medium-temperature mixed fully recycled asphalt mixture have a higher cracking risk. Therefore, crack resistance is one of the important properties of medium-temperature mixed fully recycled asphalt mixture. At present, the splitting test has been widely used at home and abroad to evaluate the cracking performance of asphalt mixtures. However, the current relevant specifications at home and abroad mostly evaluate the splitting test from the perspective of strength and strain, and lack evaluation indicators from the perspective of energy. In addition, when calculating the parameters related to the splitting performance based on the test data, it is necessary to determine the splitting stage of the specimen. The general cracking process includes three stages: crack initiation, crack propagation and failure. However, the current relevant specifications and research at home and abroad lack the judgment criteria for the cracking stage of the splitting test, and cannot be accurately evaluated and compared. In view of this, in order to accurately evaluate the cracking performance of medium-temperature mixed fully recycled asphalt mixtures, a precise identification method for the splitting process of medium-temperature mixed fully recycled asphalt mixtures is needed. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for accurately identifying the splitting process of medium-temperature mixed fully recycled asphalt mixture.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for accurately identifying the splitting process of a medium-temperature mixed fully recycled asphalt mixture, the steps of which are: (1) Obtaining Marshall specimens of medium-temperature fully recycled asphalt mixture to be evaluated; (2) A splitting test is performed on the Marshall specimen of the medium-temperature mixed fully recycled asphalt mixture obtained in step (1), and a load-vertical displacement curve and a load-loading time curve of the medium-temperature mixed fully recycled asphalt mixture are obtained by a loading machine. At the same time, a full-field strain-loading time relationship of the medium-temperature mixed fully recycled asphalt mixture specimen is obtained by a non-contact full-field strain measurement system; (3) Based on the relationship between the full-field strain and loading time of the medium-temperature mixed fully recycled asphalt mixture specimen obtained in step (2), a relationship curve between the full-field horizontal strain average value and loading time of the medium-temperature mixed fully recycled asphalt mixture specimen is calculated and obtained; (4) For the relationship curve between the average value of the horizontal strain of the medium-temperature mixed fully recycled asphalt mixture specimen obtained in step (3) and the loading time, the growth law of the average value of the horizontal strain of the whole field is divided into three stages, namely, a slow growth stage, a rapid growth stage and a decline stage. At the same time, it is determined that these three stages correspond to the crack initiation stage, the crack development stage and the failure stage respectively; (5) For the full-field horizontal strain average value-loading time relationship curve obtained in step (4), the cracking failure point is determined as the moment when the full-field horizontal strain average value reaches the maximum value, and the boundary point between the crack initiation stage and the crack development stage is determined as the boundary point between the slow growth stage and the rapid growth stage of the full-field horizontal strain average value; (6) Regarding the boundary point between the crack initiation stage and the crack development stage determined in step (5), considering that there is a certain degree of empirical judgment in determining the slow growth stage and the rapid growth stage of the average horizontal strain of the specimen, the load-loading time curve obtained in step (2) can be used to comprehensively determine the boundary point between the crack initiation stage and the crack development stage as the moment corresponding to the maximum load.
[0006] (7) Based on the moment corresponding to the dividing point between the crack initiation and crack development stages and the fracture failure point obtained in step (5) and step (6), and based on the load-vertical displacement curve obtained in step (2), a fracture test load-vertical displacement curve that accurately distinguishes the critical points of the three stages of the fracture process is obtained, and is used to calculate the relevant splitting energy parameters of the specimen.
[0007] In some embodiments, according to step (7), the cleavage energy is calculated as follows: (1) Cleavage Energy G f By splitting work W f The crack surface area is calculated according to formula (1).
[0008] In some embodiments, the splitting work W f That is, the envelope area under the load-vertical displacement curve before the crack failure point. A is the ligament surface area, which is obtained by multiplying the specimen diameter by the specimen thickness.
[0009] Compared with the prior art, the present invention has the following beneficial effects: The present invention determines the maximum value of the average value of the full-field horizontal strain as the cracking failure point of the Marshall specimen through the relationship curve of the full-field horizontal strain average value-loading time, and determines the dividing point between the crack initiation stage and the crack development stage as the dividing point between the slow growth stage and the rapid growth stage of the average value of the full-field horizontal strain, which has clear physical and mechanical significance. The average value of the full-field horizontal strain reflects the tensile deformation capacity of the specimen. In the crack initiation stage, the specimen has a large deformation resistance, so the average value of the full-field horizontal strain is relatively small; after the cracking failure point, the cracked specimen can no longer withstand more tensile cracking energy, so the average value of the full-field horizontal strain decreases accordingly, so the maximum value of the full-field horizontal strain corresponds to the cracking failure point of the Marshall specimen complete splitting test.
[0010] At the same time, compared with the distinction standards of existing specifications, the identification method of the three stages of the splitting process clarified by the present invention is more accurate and more suitable for medium-temperature mixed fully recycled asphalt mixture specimens with different splitting strengths. For example, the American AASHTO TP124-16 specification stipulates that the fracture failure point is defined as the load drop to 0.1 kN in the fracture test. There is a large error in the evaluation of the fracture performance of asphalt mixtures with large differences in fracture strength and toughness.
[0011] Details of one or more embodiments of the present application are presented in the following drawings and descriptions to make other features, purposes and advantages of the present application more concise and easy to understand. The present application is fully described and understood through the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is the full-field horizontal strain field obtained by testing based on the non-contact full-field strain measurement system; Figure 2 To identify the critical points of the three stages of the splitting process based on the relationship curve between the applied load, the average value of the horizontal strain field and the loading time; Figure 3 To distinguish the load-vertical displacement curves in the three stages of the splitting process and to calculate the splitting work. DETAILED DESCRIPTION
[0013] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0014] The present invention provides a technical solution: a method for accurately identifying the splitting process of a medium-temperature mixed fully recycled asphalt mixture, the steps of which are: (1) To prepare medium-temperature mixed recycled asphalt, a certain mass of 70# and 90# base asphalt, SBS and SBR modified asphalt were weighed, and a warm-mix performance enhancer aqueous solution was prepared. The three types of asphalt were sheared by a colloid mill for 1 min to obtain medium-temperature mixed recycled asphalt. The asphalt solid content in the medium-temperature mixed asphalt was above 60%, and the amount of warm-mix enhancer was 1%-3%.
[0015] (2) The waste asphalt mixture is kept warm at 100-120°C, the waste asphalt mixture and medium-temperature mixed recycled asphalt are added into a mixing pot, and mixed at 80-100°C to obtain a medium-temperature mixed fully recycled asphalt mixture Marshall specimen to be evaluated; (3) A splitting test is performed on the Marshall specimen of the medium-temperature mixed fully recycled asphalt mixture obtained in step (2). The load-vertical displacement curve and load-loading time curve of the medium-temperature mixed fully recycled asphalt mixture are obtained by a loading machine. At the same time, the full-field horizontal strain-loading time relationship of the medium-temperature mixed fully recycled asphalt mixture specimen is obtained by a non-contact full-field strain measurement system (such as Figure 1 shown); (4) Based on the relationship between the full-field horizontal strain and loading time of the medium-temperature mixed fully recycled asphalt mixture specimen obtained in step (3), the relationship curve between the full-field horizontal strain average value and loading time of the medium-temperature mixed fully recycled asphalt mixture specimen is calculated and obtained (e.g. Figure 2 shown); (5) For the relationship curve between the average value of the horizontal strain of the medium-temperature mixed fully recycled asphalt mixture specimen and the loading time obtained in step (4), the growth law of the average value of the horizontal strain of the whole field with time is divided into three stages, namely, a slow growth stage, a rapid growth stage and a decline stage. At the same time, it is determined that these three stages correspond to the crack initiation stage, the crack development stage and the failure stage respectively; (6) Based on the full-field horizontal strain average value-loading time relationship curve obtained in step (5), the splitting failure point is determined as the moment when the full-field horizontal strain average value reaches the maximum value, and the boundary point between the crack initiation stage and the crack development stage is determined as the boundary point between the slow growth stage and the rapid growth stage of the full-field horizontal strain average value (such as Figure 2 shown); (7) Regarding the demarcation point between the crack initiation stage and the crack development stage determined in step (6), considering that there is a certain degree of empirical judgment in determining the slow growth stage and the rapid growth stage of the average horizontal strain of the specimen, the load-loading time curve obtained in step (3) can be used to comprehensively determine the demarcation point between the crack initiation stage and the crack development stage as the moment corresponding to the maximum load (e.g. Figure 2 as shown).
[0016] (8) Based on the splitting test load-vertical displacement curve obtained in step (3), the splitting test load-vertical displacement curve that accurately distinguishes the critical points of the three stages of the splitting process is obtained based on the splitting initiation and crack development stage boundary points and the splitting failure point obtained in step (6) and step (7), and is used to calculate the relevant splitting energy parameters of the specimen (such as Figure 3 as shown).
[0017] Through the technical solution of this application, The experiments on the splitting performance of 6 groups of embodiments were conducted respectively, and the cracking performance of medium-temperature mixed fully recycled asphalt mixtures under 6 different working conditions was tested, including medium-temperature mixed asphalt with 3 regeneration agent dosages and 3 different asphalt types. The regeneration agent dosage of the fully recycled mixture was 0%, 0.1%, and 0.2%; the asphalt types were base asphalt, SBS asphalt, and SBR asphalt. The asphalt mixture gradation was AC13, and the asphalt dosage was 5.5%. Based on the above method, the maximum load and corresponding vertical displacement, cracking failure point load and corresponding vertical displacement, and splitting energy of the 6 groups of embodiments were obtained, as shown in Table 1.
[0018] In Table 1, the cleavage energy G f By the splitting work W f The fracture surface area is calculated according to formula (1).
[0019] (1) Splitting W f That is Figure 3 The envelope area under the load-vertical displacement curve before the mid-crack failure point, A is the ligament surface area, which can be obtained from the specimen diameter ( l ) multiplied by the specimen thickness ( d ) is obtained.
[0020] As can be seen from Table 1, after adding the regeneration agent, the splitting energy of the medium-temperature mixed fully recycled asphalt mixture gradually increases. After using SBR and SBS modified asphalt, the splitting energy of the medium-temperature mixed fully recycled asphalt mixture is also significantly improved, which is consistent with the conventional empirical results. At the same time, the determination of the failure point has a great influence on the calculation of the splitting energy value. The splitting energy calculated by the failure point determined by this method can clearly evaluate the cracking performance of the mixture. However, if a fixed load value (such as 0.1kN) is used as the failure point criterion, the splitting energy of the medium-temperature mixed fully recycled asphalt mixture will fluctuate greatly. Therefore, this method can accurately determine the three splitting stages of the medium-temperature mixed fully recycled asphalt mixture, which has important reference significance for accurately calculating the splitting parameters of the medium-temperature mixed fully recycled asphalt mixture and comparing the splitting performance of the medium-temperature mixed fully recycled asphalt mixture with different mechanical properties and compositions.
[0021] Table 1 Maximum load, fracture failure load and splitting energy in the splitting test of medium-temperature fully recycled asphalt mixture
[0022] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
[0023] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for accurately identifying the splitting process of medium-temperature mixed fully recycled asphalt mixture, characterized in that: The steps are: (1) Obtaining Marshall specimens of medium-temperature fully recycled asphalt mixture to be evaluated; (2) A splitting test is performed on the Marshall specimen of the medium-temperature mixed fully recycled asphalt mixture obtained in step (1), and a load-vertical displacement curve and a load-loading time curve of the medium-temperature mixed fully recycled asphalt mixture are obtained by a loading machine. At the same time, a full-field strain-loading time relationship of the medium-temperature mixed fully recycled asphalt mixture specimen is obtained by a non-contact full-field strain measurement system; (3) Based on the relationship between the full-field strain and loading time of the medium-temperature mixed fully recycled asphalt mixture specimen obtained in step (2), a relationship curve between the full-field horizontal strain average value and loading time of the medium-temperature mixed fully recycled asphalt mixture specimen is calculated and obtained; (4) For the relationship curve between the average value of the horizontal strain of the medium-temperature mixed fully recycled asphalt mixture specimen and the loading time obtained in step (3), the growth law of the average value of the horizontal strain of the whole field with time is divided into three stages, namely, a slow growth stage, a rapid growth stage and a decline stage. At the same time, it is determined that these three stages correspond to the crack initiation stage, the crack development stage and the failure stage respectively; (5) For the full-field horizontal strain average value-loading time relationship curve obtained in step (4), the splitting failure point is determined as the moment when the full-field horizontal strain average value reaches the maximum value, and the dividing point between the crack initiation stage and the crack development stage is determined as the dividing point between the slow growth stage and the rapid growth stage of the full-field horizontal strain average value; (6) With regard to the boundary point between the crack initiation stage and the crack development stage determined in step (5), considering that there is a certain degree of empirical judgment in determining the slow growth stage and the rapid growth stage of the average horizontal strain of the specimen, the load-loading time curve obtained in step (2) can be used to comprehensively determine the boundary point between the crack initiation stage and the crack development stage as the moment corresponding to the maximum load; (7) Based on the moment corresponding to the dividing point between the crack initiation and crack development stages and the splitting failure point obtained in step (5) and step (6), and based on the load-vertical displacement curve obtained in step (2), a splitting test load-vertical displacement curve that accurately distinguishes the critical points of the three stages of the splitting process is obtained, and is used to calculate the relevant splitting energy parameters of the specimen.
2. According to claim 1, a method for accurately identifying the splitting process of a medium-temperature mixed fully recycled asphalt mixture is characterized by: According to step (7), the splitting energy is calculated as: (1) Cleavage Energy G f By splitting work W f The crack surface area is calculated according to formula (1).
3. According to claim 2, a method for accurately identifying the splitting process of a medium-temperature mixed fully recycled asphalt mixture is characterized by: Splitting W f That is, the envelope area under the load-vertical displacement curve before the splitting failure point. A is the ligament surface area, which is obtained by multiplying the specimen diameter by the specimen thickness.
